Review of agile project management research through systematic literature network analysis approach - Al Jabri A.K.; Islam M.K.; Daud S.B.T. (Malque Publishing, 2025)
In the present digital era, the concepts of Agile project methodology or Agile methods have transformed technology as perceived in learning organizations. During the COVID-19 pandemic, the Agile methods domain has gained considerable attention from practitioners and researchers. While past review studies have provided valuable insights into Agile methods research, none have addressed the trends, structure, and opportunities in this domain. Therefore, this research aims to conduct a systematic review of Agile project management or Agile methods using a novel research methodology called Systematic Literature Network Analysis (SLNA). A corpus of fifty research articles from 2006 to 2023 is extracted from the Web of Science (WoS) database. The bibliometric technique has been applied to systematically collected documents. The research findings highlight that the Agile project method domain gained considerable attention during and after the COVID-19 pandemic, with most research conducted in developed countries. The outcomes suggest that future studies should focus on people and technical factors and explore different frameworks and variables to strengthen the field of Agile project methodology. These findings are valuable for future researchers, practitioners, and industry personnel. Emphasize people and technical factors while implementing Agile methods, fostering effective collaboration, and utilizing appropriate technical resources. Investigate emerging trends in Agile project management, including the impact of remote work, and conduct cross-country studies to understand the applicability of Agile methods across different contexts. The impact of Agile project management methods on society includes fostering adaptability and resilience in organizations, promoting efficient collaboration and innovation, and facilitating the successful delivery of projects that meet the evolving needs of society. A broader set of keywords, a longer time frame, and additional online databases could have resulted in a greater number of articles being analysed. ? 2024, Malque Publishing. All rights reserved.